(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The value-added of processing soybeans into Tofu and analyzing the break-even point (BEP) and the profit in the Tofu industry in the City District of Nabire Regency were objectives in research using survey research methods through structured interviews using a list of pre-prepared questions. The amount of value-added based on the Hayami Method in processed soybeans into Tofu is IDR 7.840. In contrast, the profit earned in one production process is IDR 9.602.592. The revenue is IDR 17.100.000 with the costs incurred for one time Tofu production process of IDR 7.497.408 so that the Revenue Cost Ratio value is 2.28, while the break-even point analysis results using the BEP approach were divided into two, namely Cost BEP and Production BEP. They show a value of 963 slices of Tofu and IDR 5.780.760, in which the average production will get the break-even point with a total of 963 slices of Tofu or with a production cost of IDR 5.780.760. If this amount is low, the industry will suffer losses, and if this amount is more, it will profit.